2009
DOI: 10.1063/1.3075834
|View full text |Cite
|
Sign up to set email alerts
|

Structures and stabilities of Aln+, Aln, and Aln− (n=13–34) clusters

Abstract: Putative global minima of neutral ͑Al n ͒ and singly charged ͑Al n + and Al n − ͒ aluminum clusters with n = 13-34 have been located from first-principles density functional theory structural optimizations. The calculations include spin polarization and employ the generalized gradient approximation of Perdew, Burke, and Ernzerhof to describe exchange-correlation electronic effects. Our results show that icosahedral growth dominates the structures of aluminum clusters for n = 13-22. For n = 23-34, there is a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 69 publications
(155 reference statements)
11
110
3
2
Order By: Relevance
“…All other computational details such as the pseudopotential, basis set, and the size of the fast-Fourier-transform mesh are exactly the same as in our previous work. 17,18,38,39 The accuracy of the calculations was assessed in the previous work by comparisons with the results of other first-principles techniques. An independent assessment has been provided by Henry et al 40 The optimization strategy employed to obtain the global minimum structures of anionic and neutral aluminum clusters with 35-70 atoms is also exactly the same as that employed in previous work, so we refer the reader to Ref.…”
Section: Methodsmentioning
confidence: 99%
“…All other computational details such as the pseudopotential, basis set, and the size of the fast-Fourier-transform mesh are exactly the same as in our previous work. 17,18,38,39 The accuracy of the calculations was assessed in the previous work by comparisons with the results of other first-principles techniques. An independent assessment has been provided by Henry et al 40 The optimization strategy employed to obtain the global minimum structures of anionic and neutral aluminum clusters with 35-70 atoms is also exactly the same as that employed in previous work, so we refer the reader to Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Using reactivity studies it was shown that Al 13 has superhalogen character and behaves like a single iodine atom, while Al 14 is similar to an alkaline earth atom [3,4]. Furthermore, theoretical calculations demonstrated that Al 13 -is additionally stabilized by a high symmetric icosahedral geometry [3,[5][6][7][8][9][10]. In contrast, neutral Al 13 has one electron less than needed for shell closing and was predicted to exhibit either a highly symmetric [6,[11][12][13][14] or Jahn-Teller distorted [5,9,12] decahedral or icosahedral structure.…”
Section: Introductionmentioning
confidence: 99%
“…Несмотря на то что энергетические характеристи-ки сплошных металлических кластеров рассчитывались неоднократно в различных моделях ( [15][16][17] и ссылки в них), самосогласованные вычисления энергии обра-зования вакансии в кластерах и влияние на нее кван-тования электронного спектра до сих пор не выполня-лись. Помимо этой задачи, одной из актуальных задач, которые можно сформулировать в связи с плавлением малоразмерных агрегатов, является исследование раз-мерного поведения потенциала ионизации кластеров, содержащих моновакансию.…”
Section: Introductionunclassified